PRODUCTION OF ELECTROTECHNICAL WIRE OF SCRAP AND COPPER WASTES - I. P. Volchok; A. M. Muhin (Литьë и металлургия, 2006)
Chemical composition, structure and properties of copper upon base steps of wire production technology (melting of anode copper with using of scrap and waste, electrolitical refining, producing of rod by continuous casting, manufacture of electrotechnical wire and fibres) is described.